Wireless sensor networks based smart bin. (November 2017) - Ramson, S.R. Jino; Moni, D. Jackuline
Highlights: Deployed Wireless Sensor Networks to monitor unfilled level of bins. Developed monitoring application to view the exact bin level. Surface level attainment of bins, current consumption and life expectancy of sensor nodes have been studied. Performance and quality of wireless links have been analysed. The identified system can be implemented eminently for solid waste management. Abstract: This article presents the modelling of Wireless Sensor Networks (WSNs) to monitor unfilled level of bins through a central monitoring station and evaluation of wireless links. The nodes, called Wireless Monitoring Unit (WMU) are installed in each and every bins and the sensor present in the WMU measures the unfilled level of the bins and transmit the data to the Wireless Access Point Unit (WAPU). The WAPU receives data from the WMU's and sends the data to the central monitoring station and the level of the bins are monitored by using an application. The current consumption, life expectancy of WMU and WAPU, data transmission distance between WMU and WAPU, wireless link quality and the surface level attainment between the system reading and manual reading have been compared and studied. Based on the obtained results the identified system can be implemented eminently for solid waste management. Graphical abstract: